FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT PERILAKU WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING DI TANGERANG SELATAN - JOSHUA JOSHUA; RIAN SUMARTA (Media Bisnis, 2020)
The purpose of this research is to examine the influence of knowledge, perceptions of usability, perceived of ease, security and confidentiality, experience, readiness of information technology, complexity, to the interest in the behavior of individual taxpayers in using of e-filing. This study uses primary data collected through distributing questionnaires to each individual taxpayer in the South Tangerang region. The number of samples used in this study were 110 respondents. Sampling method that used in this study is accidental sampling method. The methods that used for data analysis are reliability testing, validity test, classical assumption test, coefficient of determination test, coefficient of correlation test, simultaneous regression test (F), partial t-test. This study found that the perceptions of usability doesn’t affect the interest of individual taxpayers' behavior in using e-filing, while knowledge, perceived of ease, security and secrecy, experience, readiness of information technology, and complexity affect taxpayer behavior interest in using e-filing.